PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Zaenal Arifin, Muhammad; Sasana, Hadi (Transpublika Publisher, 2022)
This study aims to determine work discipline in the company, to determine the performance of employees at the company, to determine work discipline to the performance of employees in public services. The research method used is qualitative. The results of the research are employees who have a high level of discipline will obey all applicable regulations and will work with enthusiasm and perseverance even though the leadership does not carry out direct supervision. Discipline in carrying out duties and responsibilities in the workplace is very important and will have an impact on the performance and goals of the company in the future. The conditions experienced by employees are experiencing a decrease in employee performance, such as delays in employees coming to work at predetermined working hours and frequent absences of employees.